Information in (and not in) the Term Structure - Duffee, Gregory R. (Review of Financial Studies, 2011)
Standard approaches to building and estimating dynamic term structure models rely on the assumption that yields can serve as the factors. However, the assumption is neither theoretically necessary nor empirically supported. This article documents that almost half of the variation in bond risk premia cannot be detected using the cross-section of yields. Fluctuations in this hidden component have strong forecast power for both future short-term interest rates and excess bond returns. They are also negatively correlated with aggregate economic activity, but macroeconomic variables explain only a small fraction of variation in the hidden factor. The Author 2011. Published by Oxford University Press on behalf of The Society for Financial Studies. All rights reserved. For Permissions, please e-mail: journals.permissions@oup.com., Oxford University Press.